Exploring the meanings of children’s and adolescents’ participation through collage - Daniela Bianchi; Chiara Carla Montà; Elisabetta Biffi; Alessandro Pepe (IUL Research)
The contribution presents the results of a study on the meanings and practices of juvenile participation in decision-making processes in guardianship, using the collage approach. As made explicit in several policies, participation is crucial for the protection of minors and one of the main prevention strategies. In this framework, within broader qualitative research with a phenomenological-hermeneutic approach that questioned the meanings and practices of participation in place in the educational centres involved, we will dwell on the use of artistic language in the practice of collage as a mediator and facilitator within spaces of consultation of minors for the emergence and sharing of experiences of participation to which girls and boys were witnesses. In conclusion, it will be possible to share some considerations on the topic of child participation that are useful for guiding educational practices to make the participation of girls and boys in decision-making processes concrete.